‘The Substitution of One Piece of Nonsense for Another’: Reflections on Resistance, Gaming, and Subjugation - Willmott, Hugh (Journal of Management Studies, 2013)
Abstract This article reflects upon Willmott's 1993 article (‘Strength is ignorance; slavery is freedom: managing culture in modern organizations’) by revisiting the idea of ‘Corporate Culturism’ and its relevance for contemporary developments in management and organization, including higher education. It incorporates a commentary on how 1984 and ‘Strength is ignorance’ have been read and some reflections on the genesis of the original 1993 article. It then expands on themes in ‘Strength is ignorance’ which are of continuing relevance, and draws out implications for our research and professional lives, as scholars, working in business schools.